In Kind Solutions in The Mortgage: A comparative study - Latif Perot Ali; Sangar Ali Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
In modern jurisprudence, solutions in kind are considered as a technical means by which rights can be protected from loss, by replacing one thing with another thing as a substitute for it. However, the natural scope of the work of this idea appears clearly in real rights, especially the ancillary real rights, such as the mortgage of both types, insurance, possession, and privilege rights. And since the effect of real subrogation and its applications are clearer and more effective in the mortgage system and not in other forms of insurance, because the guarantees provided by the mortgage to the mortgagee are limited to guaranteeing non-fulfillment in the event of the debtor’s insolvency, and do not exceed other risks that the mortgagee will face, in all cases in which he exits. The thing pledged is from the responsibility of the mortgagor, and the pledgee was unable to track it, and as a result, he puts his right to the cessation of its place, and all of this necessitated the interference of another guarantee as a precautionary means to supplement this shortcoming.